Enhancing teachers’ instruction on how to study: an exploration of the effectiveness of learning strategies for particular secondary school subjects - Langbroek, Sander; Duchatelet, Dorothy; Joosten-ten Brinke, Desirée; Camp, Gino (Frontiers in Education, 2024)
Teachers’ instructions on learning strategies play a key role on how students study. However, how the effectiveness of learning strategies can be matched to different types of knowledge in a diversity of subject content has remained unexplored. In the present study, we related the effectiveness of learning strategies to different types of knowledge through an umbrella review. Furthermore, using focus-groups interviews, we explored the relation betweenthe content of school subjects andwas related to these knowledge types. We concluded that the effects of particular learning strategies vary across different learning objectives of the subjects content and we offered suggestions for the instruction of effective learning strategies.